(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This review examines the synthesis, properties, and diverse applications of polymer-grafted carbon nanotubes (CNTs). Polymer grafting onto CNTs represents a significant advancement in nanomaterial science, enhancing the functional versatility and applicability of CNTs in various fields. The synthesis methods discussed encompass both covalent and non-covalent approaches, highlighting their respective advantages in achieving tailored polymer-CNT hybrids with controlled structures and properties. The properties of polymer-grafted CNTs, including mechanical strength, electrical conductivity, and thermal stability, are critically analyzed in the context of their application potential. The synergistic combination of CNTs’ intrinsic properties with the functional attributes imparted by polymers broadens their utility in fields such as nanocomposites, sensors, biomedical devices, and energy storage systems. Key applications reviewed include the use of polymer-grafted CNTs in enhancing mechanical properties and electrical conductivity of composites, improving sensitivity and selectivity in sensor devices, enabling controlled drug delivery in biomedical applications, and enhancing performance in energy storage devices. this review underscores the transformative impact of polymer grafting on CNTs, offering insights into current advancements, challenges, and future directions in utilizing these hybrid materials across various technological domains.